THE CONCEPT OF "PLANTS" IN KAZAKH AND ENGLISH TOPONYMIC SPACE - Smatova A.E.,; Tileuberdiyev B.M.,; Meirbekov A.K.,; Turgay Han, (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of this paper is to present and exploit fundamental information, such as semantic meanings and geographical features, of phytotoponyms (a type of toponym that includes plant names) in Kazakhstan and the UK (United Kingdom). Toponymy data for this study were obtained from the place names database of Kazakhstan and the UK (United Kingdom). The results showed that the most common plant names recognisable in place names are common plants that have a close connection with daily life and positive morals in Kazakh and English culture and literature. The occurrence of plant names can reflect the characteristic plants of a city. The vegetation coverage rate where phytotoponyms are located is higher than that in non-phytotoponym areas. Altitude has a stronger correlation with the number of phytotoponyms than slope and vegetation coverage degree. The toponymic image of the world can be characterized from two sides as the relation to the ethnos (nation, nationality) and to the person (toponymic person, representative of the nation). A phytotoponym is also defined as a unit of vocabular relating to the area of spatial relationships and reflecting the location of a particular specified object.